2016
DOI: 10.1371/journal.pone.0156621
|View full text |Cite
|
Sign up to set email alerts
|

Geographical, Ethnic and Socio-Economic Differences in Utilization of Obstetric Care in the Netherlands

Abstract: BackgroundAll women in the Netherlands should have equal access to obstetric care. However, utilization of care is shaped by demand and supply factors. Demand is increased in high risk groups (non-Western women, low socio-economic status (SES)), and supply is influenced by availability of hospital facilities (hospital density). To explore the dynamics of obstetric care utilization we investigated the joint association of hospital density and individual characteristics with prototype obstetric interventions.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Finally, further research could also establish whether the association between income and obstetric care holds when looking at other perinatal outcomes such as episiotomy, use of uterine stimulants, analgesics in labor and anesthesia in migrant populations. Indeed, two studies conducted in Berlin [19,27] and one in the Netherlands [28] found differences in anesthesia provision and induction of labor between women with and without migration backgrounds. While two of them included measures of socioeconomic position (education [19,28] and neighborhood socioeconomic status [28]) none took into account the individual or household income of participants.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…Finally, further research could also establish whether the association between income and obstetric care holds when looking at other perinatal outcomes such as episiotomy, use of uterine stimulants, analgesics in labor and anesthesia in migrant populations. Indeed, two studies conducted in Berlin [19,27] and one in the Netherlands [28] found differences in anesthesia provision and induction of labor between women with and without migration backgrounds. While two of them included measures of socioeconomic position (education [19,28] and neighborhood socioeconomic status [28]) none took into account the individual or household income of participants.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…The findings that individuals with lower SES tend to receive prenatal care less frequently and are at higher risk for obstetric complications are consistent with the findings of previous studies [ 1 , 2 ]. Individuals with low SES tend to be disadvantaged in terms of medical service utilization [ 1 , 2 , 15 ]. Pregnant women with low SES have been shown to have adverse obstetric outcomes associated with inadequate prenatal visits [ 1 , 4 , 6 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with low SES tend to be disadvantaged in terms of medical service utilization [ 1 , 2 , 15 ]. Pregnant women with low SES have been shown to have adverse obstetric outcomes associated with inadequate prenatal visits [ 1 , 4 , 6 , 15 ]. The results of the current study that obstetric complications were poor in women in the MA group is consistent with the results of previous studies demonstrating that low SES is a risk factor for poor obstetric outcomes [ 1 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of general relationships between socioeconomic factors and health, we included socioeconomic factors as possible related factors, and chose the percentage of women with a bachelor's degree and the percentage of low‐income households in each prefecture based on data availability. The percentage of women aged between 20 and 44 with a bachelor's degree was calculated using the 2010 Population Census.…”
Section: Methodsmentioning
confidence: 99%